Response of nitrogen and sulphur levels on productivity and profitability of QPM hybrid (Zea mays) under dryland condition of Eastern Uttar Pradesh - JEET, SABHA; SINGH, J P; KUMAR, RAKESH; OM, HARI (The Indian Journal of Agricultural Sciences, 2014)
A field experiments was conducted during, 2009-2010 and 2010-2011 at Varanasi , under dryland condition to assess the growth, yield, quality, nutrient content and economics of QPM hybrids (Zea mays L.) under different nitrogen and sulphur levels. Twenty four treatment combination arranged in split plot design replicated three times with four nitrogen levels control, 50 kg N/ha, 100 kg N/ha and 150 kg N/ha in main plot treatments, two QPM hybrids Shaktiman-2 and Shaktiman-4 and three sulphur levels 15 kg S/ha, 30 kg S/ha and 45 kg S/ha as sub-plot treatments. Significant differences were observed among the treatments for all the parameters studied. Dry matter accumulation (g/plant), cob diameter (cm), test weight, protein content (%), protein yield (q/ha), N, P2O5, K2O and S content in plant was increased significantly as a result of nitrogen and sulphur levels. Application of 150 kg N/ha recorded significantly higher grain yield 43.94% and 43.43% over 0 kg N/ha in 1st and 2nd years, respectively. The highest net return (65.76% and 64.07%) and B: C ratio (39.08% and 38.72%) was recorded under 150 kg N/ha in 1st and 2nd years, respectively over 0 kg N/ha. QPM hybrid, Shaktiman-4 proved significantly higher growth, yield attributes, quality, net return and B: C ratio compared to Shaktiman-2. Shaktiman-4 recorded 3.55% and 2.62% higher grain yield over Shaktiman-2 in 1st and 2nd years, respectively. Application of 45 kg S/ha obtained 10.77% and 10.25% highest grain yield during 1st and 2nd years, respectively over 15 kg S/ha. The highest net return (12.56% and 11.69%) and B: C ratio (3.15% and 3.52%) was recorded under 45 kg S/ha in 1st and 2nd years, respectively over 15 kg S/ha.